Penentuan Struktur Modal Optimal Pada Perusahaan Sektor Properti, Real Estate, dan Kontruksi yang Terdaftar di Bursa Efek Indonesia - Rustam, M. (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2015)
The purpose of this study is to determine the optimal capital structure of property, real estate, and construction companies listed in Indonesia Stock Exchange. The motivation of this study is due to the current research results are still not able to answer whether the optimal capital structure exists. Based on trade-off theory, the optimal capital structure occurs when a company has a minimum capital cost. However,   it is not explained how much capital structure needed to achieve the company maximum value. In addition, this sample business sector is chosen because there are a numeours firms with an adequate long-term debt which make it possible to examine their capital structure. The method used are the nonlinear regression and Monte Carlo simulation method. These methods were chosen because the formulation of optimal capital structure is arguably complex. There are 47 samples from all property, real estate, and construction companies. The data set covered 11 years ie (2000-2010). The results showed that the optimal capital structure of properties, real estate and construction companies which are measured by the ratio between the long-term debt and equity is 0.99. Most companies of these sectors have not reached the optimal capital structure yet because the average results from these companies are 0.31.